Polifenoles Totales, Antocianinas y Capacidad Antioxidante (DPPH y ABTS) durante el procesamiento del licor y polvo de cacao - Chávez Rivera y Colls., Ronald Eduardo (2018)
This research was developed in the laboratories of (CIPNA – CIDBAM) - UNAS. The objectives were to quantify the content of total polyphenols, anthocyanins and to determine their antioxidant capacity by their ability to inhibit free radicals 1,1-diphenyl-2-picrilhydrazyl (DPPH) and 2,2 - azinobis (3etilbenzotiazoline)-6-acidosulfonic (ABTS) during the process of cocoa liquor and cocoa powder. The samples were ground and defatted by the Folch method. Hydroalcoholic extracts were prepared by weighing 10 g of cocoa in 100 mL (water / ethanol 50:50 v / v), macerating it for 24 h, filtering and centrifuging at 10000 rpm/10min/4ºC. The results were analyzed using a complete randomized design (CRD) and a complete randomized block design (CRBD), and in the treatments with statistical differences a Tukey test (p <0.05) was used using SAS version 9.0. To analyze all treatments in conjunction a principal component multivariate analysis was used using the statistical software InfoStat version 2011. The highest content of total polyphenols in the process of making cocoa liquor and cocoa powder was found in the grain with 6.394 g ± 0.095 g EAG/100 g and the lowest was found in the grounded grain with 4.036 ± 0.105 g EAG/100 g. The highest content of anthocyanins was in the grain with 1.490 ± 0.043 mg cyanidin-3-glucoside/g and the lowest was in the grounded grain with 0.074 ± 0.003 mg cyanidin-3-glucoside/g and the greatest inhibitory capacity for the DPPH radical was IC50 = 51.158 ± 0.117 µg/mL and the greatest capacity to inhibit the ABTS radical was IC50 = 34.918 ± 0.054 µg/mL.